“When reason is against a man, a man will be against reason”: Hobbes, deism, and politics - Carmel, E (2016)
This thesis explores the relationship between Thomas Hobbes and English deism. It seeks to show that Hobbes's work had a significant influence upon subsequent deists, namely, Charles Blount, John Toland, Matthew Tindal, and Anthony Collins. The thesis shows that these deists were influenced by certain distinctively Hobbesian anticlerical ideas, such as his biblical criticism, his materialism and determinism, his scepticism towards present revelation, and more. The deists, who were motivated by a similar form of anticlericalism, found in Hobbes a particularly resourceful ally. Furthermore, this thesis explores how some of Hobbes's political ideas influenced the deists: particularly his concerns regarding the dangerous role that priestly interests played in society and the instability that they generated. This thesis thus argues that Hobbes can be seen as a major influence upon English deism. Secondly, it offers an examination of Hobbes's concepts of God and reason. It shows that whilst Hobbes’s accounts of God and reason were multilayered and at times perhaps underdeveloped, they contained significant elements that anticipated the later positions of the deists. Finally, this thesis argues that for Hobbes, the rational potential of humankind, implanted by God, could be cultivated and fulfilled once peace and security are guaranteed. Thus, this thesis attempts to recover some of the more utopian aspects of Hobbes's thought. It concludes that both Hobbes and the deists were part of a project of enlightenment, but one which was not aimed against religion as such. They attempted to liberate natural reason from the darkness of corrupt clerics and their false doctrines: this was an anticlerical enlightenment that was partly initiated by Hobbes and developed significantly by the deists.